Evaluasi Program Tahfizhul Quran di Pondok Pesantren Assalaam Manado dengan Menggunakan Model CIPP - Ahmad Junaedy; Sitti Mania; Muhammad Nur Akbar Rasyid (Jurnal Ilmiah Iqra', 2023)
Evaluation of the Tahfizul Quran Program at the Assalam Manado Islamic Boarding School using the CIPP Model. This research evaluates the success of the Tahfizhul Qur’an at The Assalaam Islamic Boarding School in Manado by using the CIPP Model. The qualitative method is used to collect data through observation, interview, and document analysis. The result shows that the Tahfidzul Qur’an program has been successful with the government’s support and a supportive environment. The input evaluation shows a good assessment of human resources and facilities, although it needs some improvements. The evaluation process shows the effectiveness of the learning method and approaches in memorizing and reciting Qur’an. Product evaluation shows that this program achieves the expected goals. In conclusion, the Tahfidzul Qur’an program at the Assalaam Islamic Boarding School in Manado was successfully implemented with in-depth about success and weaknesses. Recommendations for improvement are given to increase the effectiveness and efficiency of this program, which is expected to contribute to improving knowledge and reciting Qur’an competency properly